G347 How do we think, feel, and behave towards children? developing the child attitude components scale. (May 2019) - Wolf, LJ; Maio, GR; Haddock, G; Foad, C; Costin, V; Webb, E
Abstract : Background and aims: Attitudes towards children in both private and public spheres can have serious implications for children's health because they often influence adult treatment and decision-making concerning children. However, despite the importance of attitudes towards children, psychological research has surprisingly failed to systematically examine or measure them. Addressing this gap, we developed the Child Attitude Components Scales (CACS). Methods: In pilot work, 32 adults indicated which child age-groups they spontaneously distinguished, and 119 adults indicated which feelings, beliefs, and behaviours they associated with each of the resulting child groups. We used these associations as statements and assessed the degree of adults' agreement with them. In five studies (1750 participants), we examined the structure of adults' responses, selected statements that reflected this structure, and examined the resulting scales' relationships with a range of important child-related outcomes. Results: The findings indicated that adults spontaneously distinguished between babies, toddlers, primary school children, and teenagers. Across the three younger groups, two dimensions of responses emerged consistently, with one capturing differences in positivity toward child groups and one capturing differences in stress elicited by them. As expected, the resulting ten-item measure predicted a range of relevant perceptions, evaluations, feelings, motivations, and behaviours towards the respective child group and future generations. Adults higher in the positivity category perceived these child groups as higher in warmth, competence, and innocence, were more motivated to be a parent, contributed more to a charity event benefiting children, and were generally more affectively orientated. In contrast, adults higher in the stress category were more anxious about interacting with toddlers and supported corporal punishment more. Interestingly, teenagers revealed a distinct pattern of responses: One CACS dimension captured openness to interact with teenagers, one captured positive perceptions of them and one captured positive emotions towards them. Conclusions: Together, our research shows that the CACS is a reliable and valid measure of adults' attitudes towards children. As such, the CACS can help explain and improve adult treatment and decision-making concerning children, including the development of public policy.